Testing the Co-Integration in Indian Commodity Markets: A Study with Reference to Multi Commodity Exchange India Ltd. - Babu, M.; Srinivasan, S. (Indian Journal of Finance, 2014)
This paper aims to analyze the relationship between spot and futures prices in the Indian commodity markets. There are various studies relating to testing the efficiency and cointegration of capital markets at the national and global level. An attempt has been made in this paper to test the cointegration of commodities in Multi Commodity Exchange India Ltd. using Johansen's cointegration test. The study period was from January - December 2012. A sample of 10 commodities based on their total turnover during the study period were selected. Johansen's cointegration test results reveal that the spot prices of the selected sample commodities had no influence on their futures prices.